A STUDY ON FINGERTIP DERMATOGLYPHIC PATTERN IN PATIENTS WITH MYOCARDIAL INFARCTION IN THE NORTH INDIAN POPULATION - kumari, Reenu; MAHATO, PAWAN KUMAR; YADAV, AMOD KUMAR; PANDEY, NIVEDITA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Myocardial infarction is one of the rising heart ailments causing mortality and morbidity around the world and especially in the north Indian population. In earlier studies, it has been found that dermatoglyphics and myocardial infarction have a correlation due to genetic disposition. The present study is based on the same hypothesis to find out such a relation and its uses as an economical diagnostic tool. Methods: The present study was conducted after taking informed consent forms from 150 patients with myocardial infarction as cases, whereas 150 normal health individuals were included in the study as controls. Fingerprints were taken using the method described by Cummin and Mildo. Result: The study found that the different fingerprints which are whorls, arches, and loops have a specific pattern that differs in myocardial infarction cases and control. In some cases, the loop and whorls have been increasing, whereas the arches were found to be decreasing as compared to controls. The mean total finger ridge count (TFRC) and absolute finger ridge count (AFRC) have been found to decrease in both males and females and the decrease was statistically significant. Conclusion: Dermatoglyphics and myocardial infarction have shown a close correlation due to genetic association. Thus, it can be used as one of the cost-effective diagnostic tools for myocardial infarction.